A Short Guide to Making Wax Tablets - Αntonis Vlavogilakis (EXARC Journal)
A few years ago, I conducted a series of experiments focusing on wax tablets as drawing tools in antiquity (Vlavogilakis, in press. All references to my earlier experiments with wax tablets refer to this paper). When this was over, I decided to create a diptych as a present. The method of making was inspired from examples of tablets and diptychs from different periods: Bronze Age, 8th century BC and 10th-11th century AD.